Which norms to build trust? A compass to govern the science-health-rights cycle in the life of citizens (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
At the aftermath of the pandemic laypeople and policy makers experience a common challenge. How to integrate scientific knowledge and technological advances into the decision-making processes that impact on the quality of life of everyone combining scientific soundness and public accountability. Social responsiveness of choices that lay at the basis of highly impacting policies today must be ensured. This article traces a critical path to raise some concerns and to put forth a proposal as to the governance of the science/democracy connubium. The argument herein touches upon the different levels where digital transformation disrupts the interactions between citizens (and their rights) and the healthcare sector, the interaction between medical doctors and healthcare professions on the one hand and the automation on the other hand, the interaction between efficiency and inclusiveness under the waves of technological and scientific transformation. The author ends by suggesting a model where a learning cycle is integrated at the individual as well as at the macro level.
Keywords: Trust; healthcare; automation; governance; fairness